ANALISIS KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA : Analysis of Ability to Solve Mathematics Story Problems - Amir, Nur Fadhilah; Malmia, Wa; Taufik, Taufik (Uniqbu Journal of Exact Sciences, 2021)
This study aims to determine the level of students’ abilities in (1) determining what is known, (2) determining what is asked, (3) making a mathematical model, (4) completing a mathematical model, (5) concluding answers from math story problems. The results of descriptive statistical analysis show that: (1) The ability of grade VII students of MTs Miftakhul Khair Namlea in determining what is known is categorized as high with a confidence interval of 6,96 £ m £ 7,60; (2) The ability of grade VII students of MTs Miftakhul Khair Namlea in determining what to ask is categorized as high with a confidence interval of 4,93 £ m £ 5,36; (3) The ability of grade VII students of MTs Miftakhul Khair Namlea in making mathematical models is categorized as high with a confidence interval of 9,54 £ m £ 10,67; (4) The ability of grade VII students of MTs Miftakhul Khair Namlea in solving mathematical models is categorized as low with a confidence interval of 12,93 £ m £ 21,79; (5) The ability of grade VII students of MTs Miftakhul Khair Namlea in concluding answers to math story problems is categorized as low with a confidence interval of 10,69 £ m £ 16,95.